Do patients with multiple sclerosis benefit from semi-immersive virtual reality? A randomized clinical trial on cognitive and motor outcomes. Issue 1 (2nd January 2022) - Maggio, Maria Grazia; De Luca, Rosaria; Manuli, Alfredo; Buda, Antonio; Foti Cuzzola, Marilena; Leonardi, Simona; D'Aleo, Giangaetano; Bramanti, Placido; Russo, Margherita; Calabrò, Rocco Salvatore
Abstract: Multiple sclerosis (MS) is a demyelinating disease of autoimmune originate. A large proportion of patient present with cognitive deficits that negatively affect their quality of life, thus, a proper cognitive rehabilitation is mandatory. The aim of this study is to evaluate the effect of semi-immersive virtual reality training (sVRT) on neuropsychological and motor recovery individuals suffering from MS. We enrolled 60 MS patients, randomized into either the control group (CG: 30) undergoing a conventional cognitive training, or the experimental group (EG: 30), which performed sVRT. Cognitive and motor outcomes were investigated through clinical and neuropsychological scales before (T0) and at the end (T1) of each different training. Only in the EG, we observed a significant improvement in cognitive parameters and motor scores. Our data demonstrate that VR cognitive training could potentiate MS patients' rehabilitation outcome, with positive results on both motor and cognitive performance.